A pharmacogenetic approach to improve low ovarian response: The role of CAG repeats length in the androgen receptor gene. (August 2018) - Lledo, Belén; Llácer, Joaquín; Ortiz, Jose A.; Martinez, Beatriz; Morales, Ruth; Bernabeu, Rafael
Abstract: The AR (androgen receptor) polymorphism is associated with POR risk. Furthermore, the use of androgens in POR remains controversial. Our data could clarify the effectiveness of androgen pretreatment. AR genotyping could help us to identify patients at risk for POR and POR patients that will be benefited of androgen pretreatment. Objective: The aim of this project was to investigate if the AR (androgen receptor) polymorphism could be used to identify patients at risk for POR and that will benefit from androgens pretreatment. Study Design: To evaluate the POR risk we performed a cohort study including 231 patients (54 POR and 177 control). Moreover, we included 88 IVF-cycles performed by 44 POR-patients to assess the effect on ovarian response. All patients performed two cycles: a standard ovarian stimulation and a second one with androgen preparation. We compare the results in pair from each. Results: POR showed the highest frequency of CAG repeats at 24 vs 22 in controls. Only 33% of POR have alleles with a repeat number below 23, compared with 50% of controls (p < 0.05). According to AR polymorphism ovarian response differences were shown. Patients that carried CAG repeats in AR gene between 22 and 24 showed an increased in the number of oocytes (2.61 in cycles without androgens vs 5.11 when they were pretreated with androgens; p < 0.05). For the patients that carried repeats lower than 22 and higher than 24, no differences were reported in the number of oocytes obtained in the cycle with or without androgens (2.94 vs 2.56; p = 0.88). Similar results were obtained for mature oocytes in patients that carry a number of CAG repeats between 22 and 24 (1.86 MII in cycles without androgens vs 4.04 MII when they were pretreated with androgens; p < 0.05). No differences in the number of MII oocytes were found in patients that get out of 22 and 24 repeats between the two cycles (2.31 vs 2.13; p = 0.88). Conclusion: The AR polymorphism is associated with POR risk, patients with repeats greater than 22 show a higher risk. Our data suggest that AR genotype could play a role in natural ovarian aging. Furthermore, the use of androgens in POR remains controversial. Our data suggest that the AR genotype could clarify the effectiveness of the androgen pretreatment. AR genotyping could help us to identify patients at risk of POR and POR patients that could benefit from transdermal testosterone pretreatment.